TRADISI YASINAN DAN TAHLILAN DALAM MENINGKATKAN NILAI-NILAI PENDIDIKAN ISLAM DI MASJID NUR AMANAH YOGYAKARTA - Pratama, Rido Awal (Tarbawy : Jurnal Pendidikan Islam, 2023)
This research contains the process of implementing the yasinan and tahlilan traditions at the Nur Amanah Mosque in Yogyakarta and the values of Islamic education contained in these traditions. The problems raised in this study are related to a lack of understanding of the beliefs of certain groups so that the yasinan and tahlilan traditions are considered a form of heresy. The purpose of this paper is to explain the process of carrying out the yasinan and tahlilan traditions at the Nur Amanah Mosque in Yogyakarta and explain the values of Islamic education in the aspects of faith, morals, and worship contained therein. The method used in this study is qualitative with a phenomenological approach. The results of this study conclude that the process of implementing the yasinan and tahlilan traditions at the Nur Amanah Mosque in Yogyakarta does not contain errors. This is because the readings that are applied contain the chanting of the holy verses of the Qur'an, dhikr, prayers, and prayers. The values of Islamic education in this tradition, especially in the aspect of aqidah including the six pillars of faith, the moral aspect in the form of implementing good activities, and aspects of worship such as sending prayers and banquets are included in the alms category.